Robots en quête d’auteurs - Zaven Paré (ReS Futurae)
In some theater plays, the presence of robots has replaced the costumes and special effects that previously allowed them to be staged. They begin to play their own drama for a new repertory. Born from the imagination of engineers in robotics laboratories, in the manner of telerobotized or programmed actors, they are gradually gaining their place, thanks to dramatic art and their roles. These machines question the mysteries of creation, their representation and their limits, or send us back to our image, like mirrors. This text reproduces the notes from a master class on the experience of theater with robots, at the heart of the artistic and technological challenges of the Robot Actors Project.